Does it matter who wrote the Bible?: the pastoral Implications of pseudonymity and anonymity in the New Testament - Capes, David B.; Richards, E. Randolph (Pickwick Publications, 2025)
"Students in seminary or graduate theology programs learn that some books in the Bible are anonymous. Their professors will make the point that many Pauline letters have disputed authorship and may in fact not be written by Paul. Students will also learn about the practice of pseudonymity in the world of the Bible and how some Gospels or letters are written under a false name. Now for those who become pastors or church leaders, what are they to do with what they learn? Do they teach their congregants about these authorship questions? Do they ignore that part of their training as irrelevant to the task? Do they avoid teaching or reading publicly from disputed books? Do these questions not matter in the end because the church settled on the canon? This book aims to address these pastoral challenges. An international group of scholars from universities, seminaries, and graduate theology programs convened to discuss these matters at the Lanier Theological Library in May 2022. These essays represent how many faculty are wrestling with the pastoral implications of anonymity and pseudonymity in the New Testament." --